Effect of intraperitoneal injection of Nigella sativa oil on 5-fluorouracil-induced oral mucositis in rats - Kazemi, Sohrab; Akbar Moghadamnia, Ali; Saebnouri, Homeira; Hojat Taheri Roudsari, Seyed; Sadat Afraz, Elham (Journal of Biological Studies, 2022)
Although many studies have shown that administration of Nigella sativa oil can decrease inflammation and facilitate tissue regeneration, the efficacy of its systemic administration for treatment of chemotherapy-induced oral mucositis has not been investigated. This study aimed to assess the effect of intraperitoneal injection of N. sativa oil on 5-fluorouracil (5-FU)-induced oral mucositis in rats. This study evaluated 72 healthy Wistar rats, weighing 250-300 g. The rats were randomly divided into three groups of control, placebo, and treatment (n=24). The rats received intraperitoneal injection of 5-FU on days 1 and 3. The rats’ cheek mucosa was then wounded with a linear scratch by an 18-gauge needle on day 3. The placebo and N. sativa oil were administered in groups B and C, respectively during the study period. Histological changes in oral mucosa were assessed on days 4, 6, and 8. Data were statistically analyzed using SPSS via the ANOVA, and the Kruskal-Wallis test, followed by the Mann Whitney multiple comparisons test. The mucositis score and inflammation score significantly decreased in the treatment group compared with the control and placebo groups (P<0.05). But there was no significant different between the groups regarding the connective tissue changes (P>0.05). Our findings suggest that N. sativa oil can have a notable efficacy for improvement of oral mucositis and can decrease the inflammation score in rats undergoing chemotherapy. Our results suggest that Nigella sativa can be used as a valuable remedial agent and can be a possible candidate for treatment of chemotherapy-induced oral mucositis.